2004
DOI: 10.3171/jns.2004.100.5.0867
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocephalography: a noninvasive alternative to the Wada procedure

Abstract: Although the availability of MEG is still limited across epilepsy surgery centers, this study method may be substituted for the Wada procedure in assessing hemispheric dominance for language in select cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
188
1
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(201 citation statements)
references
References 38 publications
8
188
1
4
Order By: Relevance
“…In TLE, studies using receptive language paradigms have focused on late activations (>200ms) that likely reflect sustained N400 effects. These studies have demonstrated a high concordance (approximately 90%) between MEG language lateralization and the IAP (69,(91)(92)(93)(94). Other investigators have used silent verb generation and picture naming tasks with comparable results (95,96).…”
Section: Megmentioning
confidence: 89%
“…In TLE, studies using receptive language paradigms have focused on late activations (>200ms) that likely reflect sustained N400 effects. These studies have demonstrated a high concordance (approximately 90%) between MEG language lateralization and the IAP (69,(91)(92)(93)(94). Other investigators have used silent verb generation and picture naming tasks with comparable results (95,96).…”
Section: Megmentioning
confidence: 89%
“…However, the most promising novel noninvasive methods include direct measures of physiological language activation. Some newer methods include event-related brain potentials [4] and whole-head magnetoencephalography [5][6][7]. The other alternative activation techniques are based on hemodynamic responses to language activation, such as functional transcranial Doppler [8], single-photon-emission computed tomography [9], positron emission tomography [10], near-infrared spectroscopic mapping [11], and functional magnetic resonance imaging [12].…”
Section: Introductionmentioning
confidence: 99%
“…This template of performing non-invasive MEG tests of language dominance in parallel with IAP tests (which patients were having regardless) in order to reach a conclusion regarding their suitability for surgical re-section became widely used in order to provide mounting evidence for the ability of MEG to be used as a pre-operative diagnostic tool. Papanicolaou et al (2004) measured signals in MEG from 100 epilepsy surgery candidates ranging from 8-56 years of age in response to a word recognition task. Single ECDs were used to model the activity and compute a laterality index.…”
Section: Early Epilepsy Researchmentioning
confidence: 99%